The Bobbsey twins in a TV mystery show - Hope, Laura Lee. (New York Grosset & Dunlap, 1978)
While in California appearing in a television show, the Bobbsey twins stumble upon a mystery involving a key, a missing dog, and some photographs.
Keywords: Twins -- Fiction; Actors and actresses -- Fiction; Mystery and detective stories